Students' Mathematical Reasoning Ability in the Use of RME Based on Gender and Student Motivation - Wulandari, Triana; Gunadi, Farid; Runisah, Runisah (Universitas Teknokrat Indonesia, 2025)
The problems of students' low mathematical reasoning skills, gender differences, and the low motivation to learn mathematics it is indeed a problem that occurred at the school after the observation was condusted , so a relevant learning approach is required. Realistic Mathematics Education (RME) is learning that connects mathematics with students realistic problems. This study aims to find out the differences and influence of the intersection of the use of RME on the mathematical reasoning ability of students based on gender differences and motivation. The research design used is experimental research. Data collection for the research was done using test instruments and lifts. The results showed that there were differences in mathematical reasoning skills between learning approaches and gender but not with student motivation, and there was an influence of interaction between study approaches, student motivations, and genders on students' ability to mathematically reason.The results showed that Fo (ABC) = 4,611 > Ftable = 4,040, or Ho is rejected, or there is an influence of the interaction factors learning approach, student learning motivation, and gender.